2009
DOI: 10.1177/0731684408101790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoclay on the Mechanical and Morphological Properties of Wood Polymer Nanocomposite

Abstract: Polypropylene/wood flour composites with different nanoclay and maleic anhydride grafted polypropylene (PP-g-MA) contents were fabricated by melt compounding and then by injection molding. The mechanical properties, such as flexural modulus, tensile modulus, elongation at break, and impact strength, were evaluated. Results indicated that the flexural modulus, tensile modulus, and elongation at break increases with increase of nanoclay up to 3 phc at the same concentration of PP-g-MA, and then decreases. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 33 publications
2
56
0
Order By: Relevance
“…Zabihzadeh et al 23 have reported that incorporating only 2 wt % compatibiliser into the chemi-mechanical pulp reinforced-polypropylene increased the composite tensile strength by more than 30% by changing the composite morphology and the interface between the two phases. Hemmasi et al 18 have also reported a similar behaviour for natural fibre and nanoclay filler-filled polyolefin system compatibilised with maleic anhydride-grafted co-polymers. These results show the beneficial effect of the compatibiliser and that using MaPE certainly improved the tensile properties.…”
Section: Mechanical Measurementsmentioning
confidence: 70%
“…Zabihzadeh et al 23 have reported that incorporating only 2 wt % compatibiliser into the chemi-mechanical pulp reinforced-polypropylene increased the composite tensile strength by more than 30% by changing the composite morphology and the interface between the two phases. Hemmasi et al 18 have also reported a similar behaviour for natural fibre and nanoclay filler-filled polyolefin system compatibilised with maleic anhydride-grafted co-polymers. These results show the beneficial effect of the compatibiliser and that using MaPE certainly improved the tensile properties.…”
Section: Mechanical Measurementsmentioning
confidence: 70%
“…The incorporation of 2 phc OMMT led to the increase in the flexural strength and modulus about 37 and 29%, respectively. The significant improvement in the flexural properties was related to the large aspect ratio and high interfacial contact area of the nanoparticles [10,[12][13][14][15][16][18][19][20][21][22]. As it can be clearly seen from Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 52%
“…This increment in the tensile properties was mainly attributed to the reinforcing effect of OMMT with high aspect ratio [10,[12][13][14][15][16]. It was expected that strong interfacial adhesion between polymer matrix and nanoparticles efficiently transferred the stress and improved the mechanical properties [18][19][20][21][22]. The reduction in the tensile values by further addition of OMMT (from 2 to 6 phc) could be generally explained by the agglomeration or poor dispersion of nanoparticles in polymer matrix [12-16, 18, 20-22].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However it should be noted that the negative effect of nanoclay on weathering is balanced by two phenomena. Dispersion of nanoclay as a positive effect could enhance the MOE (Hemmasi et al 2010), and also barrier properties of nanoclay decrease the water penetration into nanocomposite materials (Ashori and Nourbakhsh 2011) and then less drop of MOE occurs by decreasing of water absorption. Scientists stated that the mechanical properties of woodflour filled polymer composites are negatively affected by moisture (Stark et al 2003).…”
Section: Water Absorptionmentioning
confidence: 99%